The Role of Islamic Religious Education Teachers in Fostering Student’ Tolerance Character in Binawiyata Sragen High School - Riza, Brian Al; Inayah, Nurul Latifatul (SAINTIS Publishing, 2025)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in shaping students' tolerance character at SMK Binawiyata Sragen. Using a qualitative approach, this study examines the role of PAI teachers as facilitators, educators, coaches, and evaluators in instilling tolerance. PAI teachers not only deliver religious materials, but also guide students in understanding and applying tolerance values, both within the scope of the same religion and interfaith. The results showed that at SMK Binawiyata Sragen, religious tolerance is realized through mutual respect despite differences in sects, especially in Islam. Meanwhile, tolerance is implemented by respecting religious freedom, not imposing beliefs, and maintaining social harmony in the school environment. Islamic Education teachers play a strategic role in shaping student character through inclusive learning, a wise approach, and exemplary attitudes and behaviors. With Islamic value-based character education, students are expected to appreciate differences, maintain unity, and live harmoniously in a diverse society. This study confirms the importance of the role of PAI teachers in creating a learning environment that supports the formation of students' tolerance character.